Existence and exponential stability of periodic solution for fuzzy BAM neural networks with periodic coefficient - Dai-xi Liao; Li-hui Yang; Zhang Qian-hong (Український математичний журнал, 2011)
A class of fuzzy bidirectional associated memory (BAM) networks with periodic coefficients is studied. Some sufficient conditions are established for the existence and global exponential stability of a periodic solution of such fuzzy BAM neural networks by using a continuation theorem based on the coincidence degree and the Lyapunov-function method. The sufficient conditions are easy to verify in pattern recognition and automatic control. Finally, an example is given to show the feasibility and efficiency of our results. Вивчено клас нечiтких нейронних мереж Коско з перiодичним коефiцiєнтом. За допомогою теореми про продовження, що базується на ступенi збiгу та методi функцiй Ляпунова, встановлено достатнi умови для iснування та глобальної експоненцiальної стiйкостi перiодичного розв’язку таких нечiтких нейронних мереж Коско. Цi достатнi умови легко перевiряються при розпiзнаваннi образiв та автоматичному керуваннi. Наведено приклад, що демонструє застосовнiсть та ефективнiсть отриманих результатiв.